Image Encoding Using Multi‐Level DNA Barcodes with Nanopore Readout. Issue 28 (16th June 2021) - Zhu, Jinbo; Ermann, Niklas; Chen, Kaikai; Keyser, Ulrich F.
Abstract: Deoxyribonucleic acid (DNA) nanostructure‐based data encoding is an emerging information storage mode, offering rewritable, editable, and secure data storage. Herein, a DNA nanostructure‐based storage method established on a solid‐state nanopore sensing platform to save and encrypt a 2D grayscale image is proposed. DNA multi‐way junctions of different sizes are attached to a double strand of DNA carriers, resulting in distinct levels of current blockades when passing through a glass nanopore with diameters around 14 nm. The resulting quaternary encoding doubles the capacity relative to a classical binary system. Through toehold‐mediated strand displacement reactions, the DNA nanostructures can be precisely added to and removed from the DNA carrier. By encoding the image into 16 DNA carriers using the quaternary barcodes and reading them in one simultaneous measurement, the image is successfully saved, encrypted, and recovered. Avoiding any proteins or enzymatic reactions, the authors thus realize a pure DNA storage system on a nanopore platform with increased capacity and programmability. Abstract : Information is saved in a new way by deoxyribonucleic acid (DNA) multi‐way junctions on the carrier, a long DNA strand with multi‐binding sites. The DNA nanostructures induce multilevel current drops when they pass the nanopores. Using this quaternary encoding system, the authors save a 2D image into 16 carriers and read them out in one simultaneous measurement.